PENGARUH BESARAN HAMBATAN PEMBUMIAN TITIK NETRAL TERHADAP THD DI GEDUNG KAMPUS - Ananta Wijaya, W G Yoga; Janardana, I G N; Manuaba, I B Gede (Jurnal SPEKTRUM, 2022)
The quality of electric power is influenced by harmonic factors that occur due to an imbalance in the load on the power system. This load imbalance results in a current at the neutral point. This amount of current can cause equipment damage and loss of electrical power. Therefore, an earthing system is needed to parse the current flowing at the neutral point and as a safety for the electric power system in a building. The objective of this research was to specify the impact of the grounding resistance value of the neutral point on the current THD on the MDP installed during peak load conditions at the Electrical Engineering Campus of Udayana University in Jimbaran. This research method uses simulation with Simulink Matlab software to determine the effect of neutral point grounding resistance on current THD in areas with calcareous soils. The simulation outputs indicate that the value of the earth resistance affects the THDi value in the electrical system. The simulation outcomes represent that when the earth resistance value is 5 , the THD of the R, S, and T phase currents is feasible at 17.55%, 19.42 %, and 8.86%. Then when the resistance value is lowered by 0.5, the THD of the R, S, T phase currents is feasible 17.20%, 17.35%, and 8.79%. This shows that more slight the earth resistance number, the smaller the current THD value.